The effects of syntactic vs. semantic feature analysis of words on Iranian EFL learners' reading comprehension - Sepasdar, Mansoure; Rostampour, Mohammad (Frontiers in Education, 2022)
Learners’ semantic and syntactic knowledge of words and vocabulary development have an essential role in reading comprehension. Therefore, this study attempted to investigate and compare the impacts of instructing syntactic and semantic analyses of word features on Iranian EFL learners’ reading comprehension. Three groups were selected; one was taken as the control group and two others as experimental groups. Students in all groups took part in a reading pre-test. Two experimental groups were provided specific treatments, while the control group followed a traditional syllabus. In the end, all groups took part in a reading comprehension post-test. The results revealed that the syntactic analysis group outperformed the semantic analysis and control groups in the post-test. In addition, the participants in the semantic analysis group had a better performance than the students in the control group in the post-test. The results of this study could help teachers, learners, and textbook writers to improve reading skills in teaching, learning, and material development.